2018
DOI: 10.3390/nu10111677
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Diet, Micronutrients and the Gut Microbiota in Age-Related Macular Degeneration: New Perspectives from the Gut–Retina Axis

Abstract: Age-related macular degeneration (AMD) is a complex multifactorial disease and the primary cause of legal and irreversible blindness among individuals aged ≥65 years in developed countries. Globally, it affects 30–50 million individuals, with an estimated increase of approximately 200 million by 2020 and approximately 300 million by 2040. Currently, the neovascular form may be able to be treated with the use of anti-VEGF drugs, while no effective treatments are available for the dry form. Many studies, such as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(86 citation statements)
references
References 158 publications
(169 reference statements)
1
81
0
4
Order By: Relevance
“…We also observed that pulses had differential effects on relative levels of bacteria in the phyla Bacteriodetes (increased) and Firmicutes (decreased). Given the controversial nature of the literature indicating whether an increase in the Bacteroidetes to Firmicutes ratio is consistent with health benefits [52,[80][81][82][83][84], the importance of this observed is unclear. Nonetheless, the rank order of increase in comparison to the high-fat control diet was lentil (5-fold) > common bean (3.9-fold) > chickpea (2.9-fold) > dry pea (2.3-fold).…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that pulses had differential effects on relative levels of bacteria in the phyla Bacteriodetes (increased) and Firmicutes (decreased). Given the controversial nature of the literature indicating whether an increase in the Bacteroidetes to Firmicutes ratio is consistent with health benefits [52,[80][81][82][83][84], the importance of this observed is unclear. Nonetheless, the rank order of increase in comparison to the high-fat control diet was lentil (5-fold) > common bean (3.9-fold) > chickpea (2.9-fold) > dry pea (2.3-fold).…”
Section: Discussionmentioning
confidence: 99%
“…We highlighted that the pivotal relationship between gut microbiota and the host is involved in many intestinal disorders. Recent advances in research have demonstrated that this mutualistic gut microbiota–host relationship appears to play a critical role for many extra-intestinal diseases such as metabolic diseases and neurological disorders with “gut–brain axis” interactions [81], but also for complex multifactorial diseases such as age-related macular degeneration with “gut–retina axis” interactions [82].…”
Section: Gut Microbiota Variations In Health and Diseasementioning
confidence: 99%
“…However, the relatively weak reprogramming of the mouse by the presence of its gut microbiota may reflect the vertebrate eye's status as a site of immune privilege (17). Nevertheless, colonization has been reported to influence the mouse eye's lipid content (16), and metabolomics studies have revealed a gut-retina axis that correlates with a proclivity toward development of macular degeneration (15,78). In short, the difference between squid and mouse responses may be either due to differences in how the immune system interacts with the eye, or because of a greater need for light-organ/eye coordination in bioluminescent symbiotic associations.…”
Section: Symbiotic Regulation Of Genes Encoding Specific Functions Ocmentioning
confidence: 99%